Presence Politics Amid Disaster: Analyzing the Image Communication of Public Officials in the Handling of the 2025 West Sumatra Flood Disaster - Willandra Fahmi, Andremirza (Green Publisher Indonesia, 2026)
The 2025 West Sumatra flood and landslide disaster resulted in significant material damage, loss of life, and large-scale displacement. Beyond its humanitarian impact, the disaster also became a dynamic arena of political communication, where the on-site presence of public officials received extensive media exposure. This situation raises critical questions regarding the intersection between genuine crisis management efforts and symbolic image construction in moments of emergency.This study analyzes the political communication strategies of public officials during the 2025 West Sumatra flood and landslide disaster, with particular emphasis on image construction through physical presence at disaster locations. Employing a framing analysis approach, the research examines how verbal statements, visual imagery, and symbolic gestures are constructed and amplified within media coverage and official communication platforms. The data were collected from national news outlets, official government press releases, and social media posts of public officials during the emergency response and early recovery phases. The findings reveal that the officials’ presence at disaster sites functions not only as an administrative indicator of responsiveness but also as a symbolic performance of leadership, empathy, and crisis competence. Visual depictions—such as interacting with victims, inspecting damage, and coordinating with relief teams—serve as strategic communicative acts reinforcing narratives of care and authority. Furthermore, media framing tends to prioritize these symbolic elements over in-depth evaluation of policy effectiveness or disaster management outcomes. This pattern suggests that, in crisis contexts, political communication plays a substantial role in shaping public legitimacy, emotional resonance, and perceptions of governance performance. Ultimately, the study underscores the need to critically assess how symbolic representation can both strengthen public trust and potentially overshadow substantive policy accountability in disaster response settings.